2017
DOI: 10.1088/0256-307x/34/9/090201
|View full text |Cite
|
Sign up to set email alerts
|

Soliton Solutions to the Coupled Gerdjikov–Ivanov Equation with Rogue-Wave-Like Phenomena

Abstract: Bilinear forms of the coupled Gerdjikov–Ivanov equation are derived. The N-soliton solutions to the equation are obtained by Hirota’s method. It is interesting that the two-soliton solutions can generate the rogue-wave-like phenomena by selecting special parameters. The equation can be reduced to the Gerdjikov–Ivanov equation as well as its bilinear forms and its solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…which is only valid for β = − 1 4 corresponding to CLL system (3) and ( 4), and for β = 0 corresponding to GI system ( 5) and (6). Soliton solutions of the GI system were also studied in [47] by Hirota method. But the Hirota bilinear form of the system and so the solutions given in [47] are not correct.…”
Section: Hirota Bilinear Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…which is only valid for β = − 1 4 corresponding to CLL system (3) and ( 4), and for β = 0 corresponding to GI system ( 5) and (6). Soliton solutions of the GI system were also studied in [47] by Hirota method. But the Hirota bilinear form of the system and so the solutions given in [47] are not correct.…”
Section: Hirota Bilinear Methodsmentioning
confidence: 99%
“…Soliton solutions of the GI system were also studied in [47] by Hirota method. But the Hirota bilinear form of the system and so the solutions given in [47] are not correct.…”
Section: Hirota Bilinear Methodsmentioning
confidence: 99%
“…From Zhang et al, 26 we know that the operator Φ is hereditary and strong symmetrical and the isospectral hierarchy and nonisopectral hierarchy form an infinite-dimensional 𝜏-symmetry Lie algebra. Furthermore, the hierarchy (10) includes the Kaup-Newell equation, 27 the Chen-Lee-Liu equation, 28 the Gerdjikov-Ivanov equation, 29,30 the modified Korteweg-de Vries equation, the Sharma-Tasso-Olever equation, 31 and a new equation as special reductions. Now, let us work out the CLs from the Lax pairs.…”
Section: The Isospectral Kundu Hierarchy and Its Conservation Lawsmentioning
confidence: 99%
“…A spectral problem and the associated perturbed GI hierarchy [32] of nonlinear evolution equations is presented and shown that the GI hierarchy is integrable in a Liouville sense and possesses bi-Hamiltonian structure. Numerous efficient and influential methods have been projected for obtaining solutions of GI equation, such as algebra-geometric solutions [33], soliton hierarchy [34], bifurcations and travelling wave [35], bright and dark soliton solutions [36], Darboux transformations [37] and many more being studied for more than a decade [38][39][40][41][42][43][44][45][46][47][48], and Kaur and Wazwaz [49] obtain the optical solitons for perturbed GI equation. In this paper we are going to apply the balanced modified extended tanh-function (METF) method as a new technique to get new exact solution for the perturbed GI equation.…”
Section: Introductionmentioning
confidence: 99%